Paragrana : Internationale Zeitschrift für Historische Anthropologie (De Gruyter (A), 2008)
Paragrana is an international transdisciplinary journal edited by the Interdisciplinary Center for Historical Anthropology at Freie Universität Berlin. Freed from any attachment to an abstract anthropological norm, it explores the phenomena and structures of the human situation at the intersection of critical work in history, the humanities, and anthropology in order to develop fruitful new paradigmatic questions.